Comparative Lipidomics and microstructural characterization of Milk fat globule membrane protein powders from bovine buttermilk and cheese whey - Kuolin Si; Mengxueyao Zhang; Xuexing Zong; Yin Pei; Lu Liu; Xiuxiu Zhang; Meiling Ge; Xiaodong Li; Qingquan Yan (Food Research International, 2026)

Deep-sea bamboo corals: New Jasonisis species from Indian and Atlantic ridges and pan-oceanic genetic connectivity of Tridentisis candelabrum - Meiling Ge; Xinlong Li; Xin Tian; Ningxia Xu; Xuying Hu; Yu Xu; Zongling Wang; Xuelei Zhang; Qinzeng Xu (Deep Sea Research Part I: Oceanographic Research Papers, 2026)

Nicking-controlled biosensor: Integrating DNA Walker-RCA circuit with trimetallic nanozyme for aflatoxin B1 detection - Longsheng Jin; YuJing Liu; Wenqing Xia; Meiling Zhou; Ziying Xiao; Jingyu Ge; Xiao Yuan; Qinqiang Zhu; Meisheng Wu (Analytica Chimica Acta, 2026)

Seasonal gut microbiota and functional dynamics in brittle star (Ophiothrix exigua) from the Yellow Sea, China - Md. Tariful Islam Fuad; Yue Dong; Zhong Li; Meiling Ge; S.M. Sharifuzzaman; Xiaoshou Liu; Xuelei Zhang; Qinzeng Xu (Marine Environmental Research, 2026)

Synergistic enhancement of ionic conductivity and mechanical strength of inorganic hydroxide exchange membranes via orientation engineering for water electrolysis - Qingjie Xi; Wei Wang; Ruixiang Guo; Chenyi Zhao; Xiaofen Liu; Xiaorui Jin; Yongan Yang; Kai-Ge Zhou; Meiling Wu (Chemical Engineering Journal, 2025)

Construction of site-specific immobilized lipase in bio-inspired “rigid and flexible” composite PVIm/ZIF-8 for long-cycle biodiesel synthesis from waste cooking oil - Qian Wang; Xinyuan Zheng; Meiling Ge; Rong Chen; Fangpei Ma; Jianming Pan; Fu Yang (Chemical Engineering Journal, 2025)

Anaerobic granular sludge performance in an expanded granular sludge bed reactor treating calcium-rich wastewater by adjusting CaCO3 crystallization: Effect of upflow velocity and Ca2+ concentration - Xiaoji Liu; Dongning Pan; Quan Yuan; Xiyuan Feng; Meixuan Li; Xuening Song; Meiling Li; Yajuan Ge; Yukun Xing; Yuanzhou Yu; Zhengyu Jin (Science of The Total Environment, 2024)

Metabolic profiling of Apostichopus japonicus body wall exposed to a typical type of PBDEs: potential health risks and impact on sea cucumber health - Kui Ding; Pengji Zhuo; Meiling Ge; Xiaomei Liao; Jing Mo; Shilin Liu; Qinzeng Xu; Xuelei Zhang (Frontiers in Marine Science, 2023)
Introduction Sea cucumbers are cultivated mainly for their valuable body wall. Polybrominated diphenyl ethers are common persistent pollutants in sea waters with known impacts on aquatic animals nonetheless not yet studied for the body wall of sea cucumbers. Methods Using ltra-high performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UPLC-Triple-TOF-MS), we investigated the metabolic impact of 2,2',4,4'-tetrabromodiphenyl ether (BDE-47) on the body wall of Apostichopus japonicus . etabolite changes and metabolic pathway alterations were assessed in response to three distinct concentrations of BDE-47: 0.1 µg/L, 1.0 µg/L, and 10.0 µg/L. REsults Exposure to BDE-47 led to notable alterations in the metabolic profiles of the body wall. A total of 95~102 metabolites in the 0.1 ~ 10.0 µg/L BDE-47 treated group were altered significantly, and various disrupted metabolic pathways were identified and characterized. These metabolites and metabolic pathways were mainly involved in lipid metabolism, energy metabolism, immunity, oxidative stress, inflammation, and neurotoxicity. Discussion The findings of our study shed light on the potential health risks that polybrominated diphenyl ethers present to sea cucumbers. This underscores the imperative for both researchers and policymakers to delve deeper into further investigations and studies. These results indicate the necessity for enhanced monitoring and management practices within the sea cucumber aquaculture industry to mitigate the impact of these persistent organic pollutants and protect the health and safety of this valuable resource.

Adaptive biomineralization in two morphotypes of Sternaspidae (Annelida) from the Northern China Seas - Meiling Ge; Jing Mo; Jack Chi-Ho Ip; Yixuan Li; Wenge Shi; Zongling Wang; Xuelei Zhang; Qinzeng Xu (Frontiers in Marine Science, 2022)
Polychaetes are segmented annelid worms that play a key role in biomineralization in modern oceans. However, little is known about the underlying processes and evolutionary mechanisms. The ventro-caudal shield of Sternaspidae is a typical phosphate biomineral in annelids. Here, we investigated two sternaspids from the northern China Seas, Sternaspis chinensis and Sternaspis liui syn. n, which evolved diverse shield characteristics as local adaptation. Genetic distances, phylogenetic analyses of nuclear markers ( 18S and 28S genes), and mitochondrial genomes revealed that the latter is a junior synonym of the former. The integration of elemental composition and the transcriptomic analysis provided insights into phenotypic shield differences. The electron probe microanalysis showed that shields in S. chinensis were more biomineralized (i.e., with higher iron, phosphorus, and calcium contents) than those in S. liui syn. n. Transcriptomes of the body wall around shields determined 17,751 differentially expressed genes (DEGs) in two morphotypes of the synonymous species. Function enrichment analysis of DEGs showed that S. chinensis has an enrichment of the putative biomineralization pathways (i.e., ion transport and calmodulin binding), while S. liui syn. n consumed more energy and produced more proteins (i.e., oxidative phosphorylation and ribosome). DEGs allowed to identify seven shell matrix proteins expressed differentially in the two morphotypes, especially calponin, filamin, chitinase, and protease inhibitor BPTI/kunitz, which might contribute to shield evolutionary plasticity response to their living habitats. Overall, this study 1) revealed an environmental biomineralization adaptation in two polychaete morphotypes of one species by integrating shield chemical composition of shields and transcriptome analyses and 2) provided insights into the molecular mechanisms underlying polychaete biomineralization.

Classification of densities and characteristics of curve of population centers in China by GIS - Meiling Ge; Zhiming Feng (Journal of Geographical Sciences, 2010)